Prevalence and Characterization of Staphylococcus aureus Isolated From Retail Vegetables in China - Wu, Shi; Huang, Jiahui; Wu, Qingping; Zhang, Feng; Zhang, Jumei; Lei, Tao; Chen, Moutong; Ding, Yu; Xue, Liang (Frontiers in Microbiology, 2018)
Staphylococcus aureus is a pathogen associated with serious community and hospital-acquired diseases. The aim of this study was to investigate the prevalence of S. aureus from retail vegetables in China and then characterized S. aureus isolates by antibiotic resistance, staphylococcal enterotoxin genes, spa-typing and multi-locus sequence typing. Of 419 retail vegetable samples from 39 cities in China during 2011 to 2016, 24 (5.73%) samples were positive for S. aureus and the geometric mean was 3.85 MPN/g. The prevalence of S. aureus was highest in lettuce (13/84, 15.48%) followed by tomato (7/110, 6.36%), caraway (2/87, 2.30%), and cucumber (2/128, 1.56%), whereas other vegetables were free of S. aureus. A total of 30 isolates were analyzed. For antibiotics susceptibility test, most isolates (93.3%) were resistant to ampicillin and penicillin, whereas all isolates were susceptible to linezolid, trimethoprim/sulphamethoxazole 1:19, nitrofurantoin, rifampicin and teicoplanin. All isolates (30/30, 100%) were resistant or intermediate resistant to more than three tested antibiotics, including 9 isolates (30%) were resisted more than 10 antibiotics. Five isolates were resistant to cefoxitin and carried mecA genes which confirmed as MRSA. Of the 18 investigated SE genes, the sem gene was the most frequently detected (86.7%) followed by the sec (83.3%), sep (70.0%), seg (56.7%), sel (53.3%), seh (50.0%), seq (50.0%), sej (46.7%), seb (36.7%), sen (36.7%) and ser (33.3%) genes were harbored by more than one third of the isolates, whereas the seo and seu were detected in only 6.75% of the isolates. MLST and spa typing observed high genetic diversity in S. aureus isolated from retail vegetable in China. ST59-t437 was the predominant types (3/5, 60%) of MRSA isolates, whereas ST188-t189 was the predominant types (7/25, 28%) of MSSA isolates. Our study reflects that the retail vegetable in China could be contaminated with S. aureus but the levels of S. aureus were not very excessive. In addition, these isolates had virulence potential, most of them were enterotoxigenic and multiple antimicrobial resistance, should be draw public attention. These data have signification implications for epidemiological and public health studies of this pathogen.